FORAMINIFEROS BENTONICOS DE LA FORMACION CARMEN SILVA, MIOCENO, ISLA GRANDE DE LA TIERRA DEL FUEGO (Ameghiniana, 2013)
ABSTRACf: BENTHONIC FORAMINIFERA FROM THE CARMEN SILVA FORMATION, MIOCENE,TIERRA DEL FUEGO, ARGENTINA. 62 species of benthonic forarninifers from the type locality of the Carmen Silva Formation (Miocene, local Gaviotian Stage), Tierra del Fuego Island, are illustrated, inclucling two new species: Robertinoides australis and Gavelinella cagnoni and a new subspecies: Trifarina angulosa fueguina. The fauna studied exhibits strong dominance. The following species were found consistently and frequently, in the lower member (proclelta pelites): Noionella auris, Florilus deceptrix, Epistominella exigua, Trifarina angulosa fueguina, "Buccella" sp.; and in the upper member (delta front sediments): Astrononion echolsi, Gavelinella cagnoni and Quinqueloculina seminulum.